KUALITAS PENERAPAN GOOD CORPORATE GOVERNANCE PADA BANK UMUM SYARIAH DI INDONESIA SERTA PENGARUHNYA PADA KINERJA KEUANGAN - Dwi Nur'aini Ihsan (Universitas Muhammadiyah Prof Dr Hamka, 2016)
This study aimed to examine the effect of CAR, NPF, ROA, ROE, FDR AND BOPO to GCG at Islamic banks the period 2010 - 2014. The aim of this study was to determine how the GCG influence on the financial performance of Islamic banks. The data used is secondary data obtained from the publication of the Annual Report of Islamic Banks and Annual Report GCG.Selection of the samples in this study using purposive sampling method and obtained 10 Islamic banks that match the criteria. The method used in this research is panel data regression analysis and found that the more appropriate model uses regression random effect model. From the results, the value of R-Square is 33.83%. Partially indicates that the variable CAR AND BOPO positive significant effect on the GCG with each regression coefficient of 2.146 and 2.654.